THE MOVEMENT OF DISPERSED MATERIALS IN TILTING ROTARY FURNACES - S. L. Rovin (Литьë и металлургия, 2016)
The article presents the results of a study of the movement of dispersed materials in tilting rotary furnaces. The proposed scheme describes a complex helical reciprocating movement of materials in rotary tilting furnaces that are designed for recycling of dispersible metal-containing wastes.